Impact of Modernization of Agricultural Technology on Stratification and Social Mobility in Farming Communities - Nevi Dwi Kirana (Department of Sociology Faculty of Social and Political Sciences, 2022)
The existence of technological advances in the agricultural sector has made major changes to the condition of society, especially when it comes to farmers. This modernization led to a rapid increase in agricultural production. However, it also has an impact on the welfare of poor farmers. This study uses a literature study research method. This study uses data collection techniques using secondary data. The data is then analyzed using the stage model from Nazir and Arikunto. The results of this study indicate that the modernization of technology in the agricultural sector has had an impact on the stratification of the farming community. Some of those who feel they have no life welfare choose to switch professions. This profession shift causes these farmers to carry out social mobility and status changes in their social stratification.